Aplikasi Pengeluaran Kas Belanja Bulanan Pada Administrasi Sekretariat Daerah Kabupaten Kubu Raya Berbasis Website - Nanda Diaz Arizona; Rafika Rafika (Jurnal Sistem Informasi Akuntansi, 2020)
In the process of cash disbursement in the Regional Secretarial Administration section of the Kubu Raya Regency, the main source of the problems that the authors encountered, in the ongoing information system there are still deficiencies, namely, the absence of use of programs or applications in data processing, especially data collection of monthly cash expenditures and reports. finance so that often there are errors in calculating or looking for data that has not been or has been issued, the risk of errors in recording transactions for monthly cash expenditures. For companies, this application can be used as a balancing material in determining future company policies and can be an input to help the company run smoothly, especially in the part of recording monthly cash expenditures with a computerized system. The results of the application of the design and construction of cash disbursements that are built are expected to help improve the performance of cash disbursements processing in the Regional Secretarial Administration of Kubu Raya Regency.